Earth‐Abundant and Durable Nanoporous Catalyst for Exhaust‐Gas Conversion. (3rd February 2016) - Fujita, Takeshi; Abe, Hideki; Tanabe, Toyokazu; Ito, Yoshikazu; Tokunaga, Tomoharu; Arai, Shigeo; Yamamoto, Yuta; Hirata, Akihiko; Chen, Mingwei
Abstract : Precious metals (Pt and Pd) and rare earth elements (Ce in the form of CeO2 ) are typical materials for heterogeneous exhaust‐gas catalysts in automotive systems. However, their limited resources and high market‐driven prices are principal issues in realizing the path toward a more sustainable society. In this regard, herein, a nanoporous NiCuMnO catalyst, which is both abundant and durable, is synthesized by one‐step free dealloying. The catalyst thus developed exhibits catalytic activity and durability for NO reduction and CO oxidation. Microstructure characterization indicates a distinct structural feature: catalytically active Cu/CuO regions are tangled with a stable nanoporous NiMnO network after activation. The results obtained by in situ transmission electron microscopy during NO reduction clearly capture the unique reaction‐induced self‐transformation of the nanostructure. This finding can possibly pave the way for the design of new catalysts for the conversion of exhaust gas based on the element strategy. Abstract : An earth‐abundant and durable nanoporous catalyst is developed for exhaust‐gas conversion. The nanoporous NiCuMnO catalyst obtained by one‐step dealloying exhibits high catalytic activity and durability for NO reduction and CO oxidation. The catalytically active Cu/CuO regions are tangled with a stable nanoporous NiMnO network, indicating a new catalyst design. The nanoporous catalysts may be a rational alternative to traditional precious‐metal catalysts.